Odontochilus napoensis sp. nov. (Orchidoideae: Orchidaceae) from southwestern Guangxi, China. (29th March 2016) - Tang, Huan; Feng, Hui‐Zhe; Huang, Yun‐Feng
Abstract : Odontochilus napoensis, a new species from southwestern Guangxi, China, is described and illustrated. It is close to Odontochilus inabae (Hayata) T. P. Lin, but can be distinguished by its glabrous ovary, solitary flower, and 2.0–3.5 mm long filaments of flanges. It is also similar to O. nanlingensis (L. P. Siu & K. Y. Lang) Ormerod, but differs by the solitary, not resupinate flower, and light greenish–brown lateral sepals.